2021
DOI: 10.1002/open.202100239
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization and Antimicrobial Properties of Nanosized Silver‐Containing Carbon/Silica Composites from Rice Husk Waste

Abstract: Rice husk, one of the main side products in the rice production, and its sustainable management represent a challenge in many countries. Herein, we describe the use of this abundant agricultural bio‐waste as feedstock for the preparation of silver‐containing carbon/silica nano composites with antimicrobial properties. The synthesis was performed using a fast and cheap methodology consisting of wet impregnation followed by pyrolysis, yielding C/SiO2 composite materials doped with varying amounts of silver from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 71 publications
(56 reference statements)
0
2
0
1
Order By: Relevance
“…Some studies have reported that silica interacts with bacterial cell membrane proteins, altering their function and creating channels for the entry of antimicrobial agents, which are typically combined with silica nanoparticles (Tian and Liu, 2021). For example, Unglaube et al developed carbon-based and silver-containing silica composites from rice husk waste: the nanomaterial showed outstanding activity against K. pneumoniae, A. baumannii, E. faecium, S. aureus, P. aeruginosa, E. coli, and the pathogenic yeast C. albicans (Unglaube et al, 2021). Similarly, Al-Asmar et al, employed mesoporous silica nanoparticles in pectin films to extend the shelf-life of strawberries and control the presence of microorganisms (Al-Asmar et al, 2020).…”
Section: Antimicrobial Mechanisms Of Inorganic Nanoparticlesmentioning
confidence: 99%
“…Some studies have reported that silica interacts with bacterial cell membrane proteins, altering their function and creating channels for the entry of antimicrobial agents, which are typically combined with silica nanoparticles (Tian and Liu, 2021). For example, Unglaube et al developed carbon-based and silver-containing silica composites from rice husk waste: the nanomaterial showed outstanding activity against K. pneumoniae, A. baumannii, E. faecium, S. aureus, P. aeruginosa, E. coli, and the pathogenic yeast C. albicans (Unglaube et al, 2021). Similarly, Al-Asmar et al, employed mesoporous silica nanoparticles in pectin films to extend the shelf-life of strawberries and control the presence of microorganisms (Al-Asmar et al, 2020).…”
Section: Antimicrobial Mechanisms Of Inorganic Nanoparticlesmentioning
confidence: 99%
“…Sekam adalah lapisan keras yang terdiri dari lemma dan palea. Sekam padi merupakan produk sampingan dari produksi padi (Unglaube et al, 2021). Sekam padi tersusun dari selulosa sebanyak 40 %, lignin sebanyak 30 % dan 20 % silika Kandungan silika yang tinggi dan harga komoditas yang ekonomis menjadikan sekam padi sebagai bahan baku industri (Mezan et al, 2021).…”
Section: Pendahuluanunclassified
“…[1,2] The management of this amount of waste represents a challenge for most communities, being the current 'solution' the openfield burning of the biomass, resulting in huge amounts of green-house gas and particulate emissions to the atmosphere, which is associated with major health issues. [3 -5] With the aim of finding a more sustainable use of these residues, our group recently developed ways to valorize rice husk waste (RH) to prepare new materials with bio-medical, [6] and catalytical applications. [7,8] Our general strategy is to exploit the ability of pyrolyzed RH to act simultaneously as Brønsted-and Lewis-acid, and supporting metal nanoparticles onto its surface, thus conferring these composites antimicrobial and catalytic properties.…”
Section: Introductionmentioning
confidence: 99%